Matching conditions for values of characteristic oblique derivative at the end of a string, initial data and right-hand side of the wave equation - Ustilko, Ekaterina V.; Lomovtsev, Fiodar E. (Journal of the Belarusian State University. Mathematics and Informatics, 2020)
Sufficient matching conditions the time-dependent characteristic first derivatives in the boundary mode with the initial conditions and the more general vibration equation of a semi-bounded string are derived in the sets of solutions of all higher order smoothness orders. They generalize the previously found sufficient matching conditions in the case of a similar mixed problem for the simplest string vibration equation. The characteristic of non-stationary first oblique derivatives in the boundary mode means that at each moment of time they are directed along the critical characteristic.
Keywords: mixed problem; characteristic first oblique derivative; initial conditions; smoothness requirements; matching conditions